1991
DOI: 10.1159/000282265
|View full text |Cite
|
Sign up to set email alerts
|

Combined Therapy of Interleukin 2 with Cyclophosphamide or Bacillus Calmette-Guérin against Implanted Bladder Cancer Cells in Mice

Abstract: 1 × 105 cells of FAMFT-induced bladder cancer cell line (MBT-2) were injected into the right leg of the C3H/He mice. 10 days later, these animals with the same tumor size were divided into four groups. Group 1 is the control with no treatment. Group 2 underwent interleukin 2 (IL-2) treatment for 10 days since the 11th day after tumor inoculation. Group 3 received just one CPM injection on the 10th day. Group 4 had a combination therapy of CPM, followed by IL-2. Group 1 and 2 exhibited enl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In gener al, CY strongly inhibits the function of immunocompe tent cells at a dose that manifests direct antitumor effects ( 150 mg/kg). Therefore, the dose should be reduced to 2-50 mg/kg when anticipating its use as a BRM [9,10,13,[20][21][22], By combining IL-2 and CY, an increase of NK and LAK activity, and survival prolongation of tumor bearing mice is obtained [13,14,[20][21][22][23][24], Kan et al [22] pointed out that the administration sequence of IL-2 and CY was important, because it may deplete the effector cells when CY is administered after IL-2 administration. On the other hand, with the administration sequence of CY and IL-2, suppressor T cell function was inhibited and antitumor activity was enhanced [23,25].…”
Section: Discussionmentioning
confidence: 99%
“…In gener al, CY strongly inhibits the function of immunocompe tent cells at a dose that manifests direct antitumor effects ( 150 mg/kg). Therefore, the dose should be reduced to 2-50 mg/kg when anticipating its use as a BRM [9,10,13,[20][21][22], By combining IL-2 and CY, an increase of NK and LAK activity, and survival prolongation of tumor bearing mice is obtained [13,14,[20][21][22][23][24], Kan et al [22] pointed out that the administration sequence of IL-2 and CY was important, because it may deplete the effector cells when CY is administered after IL-2 administration. On the other hand, with the administration sequence of CY and IL-2, suppressor T cell function was inhibited and antitumor activity was enhanced [23,25].…”
Section: Discussionmentioning
confidence: 99%
“…However, without TV, in vivo manipulation with either CYC or IL-2 alone or their combination offers no immunostimulative effect. We had previously reported that early injection of IL-2 (500 units/mouse), starting from 3 days after tumor inoc ulation, was unable to suppress the growth of MBT-2 tumor [16,17], In contrast, the combination therapy of CYC with TV not only significantly suppresses the tumor growth but also prolongs the survival of the mice with or without IL-2. But, without CYC, the combination treat ment of TV and IL-2 exhibits no tumor suppression effect.…”
Section: Discussionmentioning
confidence: 97%
“…Using the same C3H/He-MBT-2 tumor model treated by a single dose CYC (100 mg/kg i.p.) injection 10 days after tumor inoculation, Wada et al [17] reported that tempo rary reduction in tumor volumes was observed, but regrowth of the tumor occurred. This indicates that early CYC treatment may temporarily suppress the tumor growth by its direct tumoricidal effect instead of success fully enhancing the host's specific antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%